PENGARUH PBV, DPR, ROE, DAN EPS TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Dhimas Arvico, 13.05.52.0138; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2017)
This study aims to examined and analyzed the effect of PBV, DPR, ROE, and EPS to stock return on manufacturing companies listed in the Indonesia Stock Exchange.The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2011-2014 that reported complete annual report and published in Indonesian Capital Market Directory. Samples are included in the criteria of this study were 160 companies using purposive sampling method. This research data analysis methods using the multiple linear regression analysis. The results showed that EPS have positive effect toward stock return. Whereas PBV, DPR, and ROE not significance on the stock return.Keywords: Price Book Value, Divident Payout Ratio, Return On Equity, Earnings Per Share and Stock Return